"Transforming Higher Education: Exploring the Impact of NEP 2020 Implementation in India" (International Journal of Food and Nutritional Sciences, 2022)
The National Education Policy (NEP) 2020, a landmark reform in India's education sector, has ushered in a paradigm shift in the approach to higher education. This research paper delves into the multifaceted impact of NEP 2020 on higher education institutions, students, and the educational ecosystem as a whole. Drawing on a synthesis of qualitative and quantitative data, this study examines the policy's implementation and assesses its implications across various dimensions.The paper commences with a contextual exploration of NEP 2020's key principles, such as holistic education, multidisciplinary learning, and technology integration. It then delves into the tangible effects of these principles on higher education institutions. The study explores how institutions are adapting their curricula, teaching methodologies, and assessment approaches to align with the policy's goals. The impact on faculty development, infrastructure enhancement, and financial sustainability is also analysed, shedding light on the challenges and successes encountered.The policy's effect on bridging regional disparities and addressing the digital divide is explored, highlighting both achievements and areas needing further attention. The study also assesses the interplay between autonomy and regulation in higher education institutions, uncovering the complexities of maintaining educational standards while fostering innovation.The research culminates in an evaluation of the unintended consequences that have emerged post-NEP 2020 implementation, such as challenges related to the assessment of practical skills, the adaptability of specialized institutions to multidisciplinary approaches, and the need for continued professional development for educators.